Women in the National Guard: Coping and Barriers to Care. (January 2017) - Maung, Joanna; Nilsson, Johanna E.; Berkel, LaVerne A.; Kelly, Patricia
Abstract : This study involved interviews with 42 women from the National Guard about their experiences of coping during reintegration into civilian life. Data were analyzed using techniques of conventional content analysis. The 1st theme that emerged regarded barriers to seeking and accessing care (institutional barriers, personal barriers, and stigma). The 2nd theme, coping strategies, consisted of 4 categories (seeking or gaining professional help, seeking social support, using routine activities, and using aspects of religion/spirituality). Implications for clinical work with returning female soldiers are discussed.